A simple acidic 'turn-on' fluorescent pH probe based on BOPYIN and its visual detection and cellular imaging. (June 2020) - Yuan, Xiaohui; Zhang, Tingting; Yan, Jiaying; Chen, Xi; Wang, Long; Liu, Xiang; Zheng, Kaibo; Zhang, Nuonuo
Abstract: A simple high selective and sensitive fluorescent pH probe based on a new seven-membered BOPYIN ( BO rondifluoride-3, 3-dimethyl-2-[2-(2- PY rrolyl) ethenyl] IN dole, Probe-NH 2, Scheme 1) has been designed and synthesized. With the increase of acidity (pH from 5.51 to 2.47), the emission intensity dramatically enhanced to strong fluorescence. The linear response range is from 5.5 to 3.0 with p K a  = 3.63, which is suitable for pH detection in biological system. Moreover, this probe has excellent selectivity response to H +, short response time (less than 10 s), reversibility and low cytotoxicity. Possible sensing mechanism studies demonstrated that the linear response of the probes to acidity of solution is the conjugation of H + with response site N atom in primary amino group on BOPYIN. Besides, the fluorescent change of the Probe-NH 2 relies on PET and/or ICT process which is proved by experiment and further confirmed by DFT theoretical calculation. Finally, the probe has been successfully applied for visual detection and cellular imaging. Graphical abstract: Image 1 Highlights: A novel BOPYIN based 'turn-on' fluorescent probe for acidic pH was developed. The PET/ICT mechanism is confirmed by spectra and DFT calculations studies. There is no significant interference caused by common metal ions to this pH probe. This probe can be used in real-time and reversible pH sensing. Applications were carried out for visual detection and cellular imaging.